V2X Technology in Metro trains using Internet of Things (IOT) and Automatic Train Supervision (ATS) for smart cities - Viswanathan, Vidya; Theresal, T.; Dhanapal, S. (IJRDO -Journal of Computer Science Engineering, 2017)
The concept of intelligent transportation system(ITS) will be built on the foundation of vehicle-to-vehicle(V2V) and vehicle-to-infrastructure (V2I) technology. Thesystem will ensure communication between vehicles andthe infrastructure. This technology introduces radiobasedsystems that can see “beyond the sensors” range toaugment the information provided by the vehiclesadvanced driver assist systems (ADAS). This collection oftechnology marks a new era in vehicle communication.The metro trains operate through Automatic TrainSupervision (ATS). The system has the capability tosupervise and organize the train movements continuouslyin an optimum manner. The main function of ATS systemis automatic management of train movement with dueinterfacing with the Automatic Train Protection(ATP)/Automatic Train Operation (ATO)/ ComputerBased Interlocking (CBI) systems for automatic routesetting and train regulation. The whole idea of interfacingV2X technology with the centralized ATS using IOT is tocreate opportunities to mine the accumulated data toprovide new services by applying intelligent analytics.